ANALISIS BEBAN KERJA MENTAL MENGGUNAKAN NASA-TLX - Sambudi Hamali; M Firza Madani; Arnetta Pangestu; Elia Permata Sari (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2022)
This study aims to measure the level of mental burden experienced by machine operators in food and beverage companies. The study used the Nasa-TLX method, with a total sample of 8 operators in the mini jelly production section. The results of the research show that the operator's mental workload is high. Therefore, companies must take action to reduce the high mental burden of operators for the good of employees and the company